La obra de arte como elemento estético y cuestionador social - Miño Palacios, David Salomon (2018)
The beginning of the nineteenth century, with the creation of new means of transportation, and the growing society the industrial revolution arose, was without doubt the starting point of commerce on a larger scale, which allowed the individual to get to know the first steps of consumerism which has as its outcome a branch in what is now known as noise pollution. The industrial development prompted a strong economic activation, said alteration favored the society of the time to better the quality of life, with the creation of various sources of work, everything seemed to be working properly but it was undeniable that the natural balance of the ecosystem was being modified and the change would be reflected a century later. Currently discussing the noise or noise pollution is a topic that takes importance according to the context in which it focuses. For example, the European Union has different measures to those made in South America, taking into account that there are regulations in both continents. In Ecuador, the problem is more alarming with laws that society is totally unaware of due to the lack of information on the part of the state which is reflected in the GAD (decentralized autonomous government) of each province of the country. The exploration of this work has raised an artistic intervention focused on a video art which allows us to demonstrate in a subtle and necessary way the growing problematic of our society, registering each one of its emotions in such a way that it seems invisible to the human being. visible in a desperate cry of alertness and confusion embodied in a sequence of images and sounds. The manifestation or intervention artist, is a necessary action in this field of art where we can collect emotions that connect the artist and the viewer in a close link between concepts, perceptions, feelings and needs, at the time of carrying out the work in a search of bewilderment and questions that becomes a trunk of timely records. In the construction of this work sectioned by stages, it is intended to acquire theoretical concepts that allow debating the problem and raise it or place it in a point of national social interest, in which each of the daily activities carried out by the human being is analyzed, which generates conflicts of use such as the health problems generated by the apparently invisible type of contamination that leaves traces and high risk sequelae for people who are in direct contact with this exhibition. From this perspective, we take contemporary art from two perspectives, the first as an element or questioning medium between the work and the public that generates and fulfills the theoretical purposes of art. In the words of Danto, the ancestral prototype of art has been mimesis. And the second to create or promote urban spaces where art can be transmitted from its various ramifications and articulations that converge at a point where the only point of interest is the culturalization of Orense society.